Experiencias de los estudiantes de estomatología en el control de la conducta de niños. Analisis cualitativo. - Ramos, Marisel (My University, 2019)
Objective of the study is to know the experiences of stomatology students in relation to the control of the behavior of the pediatric patient. Methodology. For this, a qualitative analysis was carried out in a transcendental phenomenological approach. Why the interview was conducted to all students who met the selection criteria to obtain the saturation of the information. The method of data collection was approved by Marshall C1, and the interview following the approach of Seidman I 2 that recommends conducting three separate interviews to participants. Results. The information obtained through interviews and videos was analyzed through the Atlas.Ti computer program. Where the lack of confidence of the students at the time of attending pediatric patients is obtained as results. And how this confidence is acquired at the moment of carrying out their pre-professional practices guided by the teacher. Conclusions. It is concluded that the student can not acquire sufficient skills to achieve control of the child’s behavior at the time of dental care, despite having the theoretical knowledge.
Objetivo del estudio es conocer las experiencias de los estudiantes de estomatología en relación al control de la conducta del paciente pediátrico. Metodología. Para ello fue realizado un análisis cualitativo empleado un enfoque fenomenológico de tipo trascendental. Para lo cual se realizó la entrevista a todos los estudiantes que cumplieron los criterios de selección hasta obtener la saturación de la información. El método de recolección de datos fue la entrevista recomendado por Marshall C 1, y la entrevista siguiendo el enfoque de Seidman I 2 que recomienda realizar tres entrevistas por separado a los participantes. Resultados. La información obtenida a través de entrevistas y videos fue analizada a través del programa informático Atlas.Ti. Conclusiones. Se concluye que el estudiante no adquiere las habilidades suficientes para lograr el control de la conducta del niño al momento de su atención odontológica, a pesar de tener los conocimientos teóricos.
Keywords: ESTUDIANTES; CONTROL DE LA CONDUCTA; NIÑOS; ANÁLISIS CUALITATIVO